THE INFLUENCE OF FLEXIBLE WORK POLICIES ON WORK-LIFE BALANCE AND EMPLOYEE PRODUCTIVITY - Suherman, Asep (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Work flexibility has become an important issue in human resource management, especially in the context of changing work dynamics due to the COVID-19 pandemic. This research aims to explore the influence of flexible work policies on work-life balance and employee productivity, as well as the challenges faced in their implementation. This study focuses on analyzing the relationship between flexible work policies, work-life balance, and employee productivity in various organizational contexts. This research uses a Systematic Literature Review (SLR) approach to collect and analyze data from 46 relevant peer-reviewed articles. The analysis process was carried out using coding techniques and thematic analysis to identify main patterns and themes. Findings show that flexible work policies significantly improve employee work-life balance and productivity, especially when supported by an inclusive organizational culture and strong managerial support. However, challenges such as work-family conflict and lack of technological support were also identified. This research makes an important contribution to the development of theory and practice in human resource management, by emphasizing the need for policies that are adaptive and responsive to employee needs. These findings can help organizations design more effective strategies to improve employee well-being and organizational performance.